PERAN PELATIHAN TIK MTS TERHADAP HASIL TES AKHIR PEMBELAJARAN: (Penelitian pada Pelatihan TIK MTs di Kankemenag Kota Bekasi dan Kankemenag Kabupaten Ciamis) - Saeful Nurdin (WIDYABORNEO, 2021)
On-the-job Training (PDWK) ICT MTs is a training program as a medium of knowledge and skills used in conveying information or messages in an interactive form. The purpose of this study is to determine the role of information communication technology, the method used is descriptive quantitative method. This research was carried out in the Work Areas of the Ministry of Religion of Bekasi City and the Ministry of Religion of Ciamis Regency, the sample of the study was 60 teachers in the field of study at Madrasah Tsanawiyah in the Ministry of Religion of West Java Province. From the analysis results, the significance value is smaller than 0.05, that is, 0.027 < 0.05, then the data group of PDWK ICT MTs Bekasi City with PDWK ICT MTs Ciamis Regency has different variants. Analysis of the t-test obtained a significance value of t-count is 0.378 and t-table is 2.002, where t-count is smaller than t-table, it can be concluded that there is no difference in the average test scores at the ICT PDWK in the Ministry of Religion, Bekasi City with the average test scores at the PDWK. ICT in the Ministry of Religion of Ciamis Regency.